1997
DOI: 10.1021/jm970011b
|View full text |Cite
|
Sign up to set email alerts
|

Address and Message Sequences for the Nociceptin Receptor:  A Structure−Activity Study of Nociceptin-(1−13)-peptide amide

Abstract: Nociceptin (NC) and some of its fragments as well as nociceptin-(1-13)-peptide amide [NC- (1-13)-NH2] and a series of its analogues were prepared and tested in the mouse vas deferens in an attempt to identify the sequences involved in the activation (message) and in the binding (address) of nociceptin to its receptor. The NC receptor that inhibits the electrically evoked twitches of the mouse vas deferens was demonstrated to be distinct from the delta opioid receptor, since naloxone and Dmt-Tic-OH (a selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
177
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(188 citation statements)
references
References 28 publications
11
177
0
Order By: Relevance
“…Another reason for a lack of response in the nociceptin system could be that LPS-induced sepsis does not activate the relevant pathways or transcription factors involved in upregulation of NOP and ppN/OFQ transcripts. Furthermore, the use of LPS as a model has been criticised for failing to reproduce physiological events that occur in human sepsis [9] and is therefore not considered as clinically relevant as other models. For these reasons, we recommend that in vivo research into the nociceptin system during sepsis employs the use of a longer term polymicrobial model of sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason for a lack of response in the nociceptin system could be that LPS-induced sepsis does not activate the relevant pathways or transcription factors involved in upregulation of NOP and ppN/OFQ transcripts. Furthermore, the use of LPS as a model has been criticised for failing to reproduce physiological events that occur in human sepsis [9] and is therefore not considered as clinically relevant as other models. For these reasons, we recommend that in vivo research into the nociceptin system during sepsis employs the use of a longer term polymicrobial model of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…The peptide NOP antagonist UFP-101 was synthesized by the group of Guerrini and Calò, (University of Ferrara, Italy), as previously described [9] and suspended in phosphate buffered saline (PBS). UFP-101was used in similar doses to previous studies in a mg/kg conversion dose for mice [3,6].…”
Section: Methodsmentioning
confidence: 99%
“…In earlier reports, it has been demonstrated that NC(1-13)NH 2 was the shortest fragment that retained the full bioactivities of NC [4,5]. Taking NC(1-13)NH 2 as a template, a series of analogues were designed and synthesized to study the structure-activity relationship of the N-terminal tetrapeptide of NC [2,3,6,14].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic structure-activity study of the activity of NC fragments determined NC(1-13)NH 2 to be the minimal sequence that retains full agonist activity [4], and NC(1-13)NH 2 has served as a template for the designing of further compounds since then. The subsequent studies on NC-related peptides revealed that, as in case of opioid peptide, the message domain of NC coincides with the N-tetrapeptide F-G-G-F, then leaving to the highly basic C-terminal sequence NC(5-13) the function of address domain [5]. The compound [Phe 1 (CH 2 -NH)Gly 2 ]NC(1-13)NH 2 was synthesized in an attempt to protect the N-terminus from degradation by aminopeptidases and it was found to behave as an OP 4 antagonist in a variety of in vitro assays, while acting as an agonist or partial agonist in most in vivo assays [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Selective agonists DPDPE (Mosberg et al, 1983), DSBULET (Delay-Goyet et al, 1988), [DAla 2 ]deltorphin I or II (Erspamer et al, 1989), SNC80 (Bilsky et al, 1995) U69593 (Lahti et al, 1985), CI977 (Hunter et al, 1990), Salvinorin A (Roth et al, 2002) Endomorphin-1 and -2 (Zadina et al, 1997), morphine (Goldstein and Naidu, 1989), DAMGO (Handa et al, 1981), sufentanil (Yeadon and Kitchen, 1988), PL017 (Costa et al, 1992) N/OFQ, N/OFQ-(1-13)-NH2 (Guerrini et al, 1997), Ro646198 (Jenck et al, 2000), UFP-112 (Rizzi et al, 2007) Selective antagonists Naltrindole (Portoghese et al, 1988), naltriben (Sofuoglu et al, 1991) Nor-binaltorphimine (Portoghese et al, 1987), GNTI (Stevens et al, 2000) CTAP (Pelton et al, 1986) J113397 (8.3, Kawamoto et al, 1999, SB612111 (9.5, Zaratin et al, 2004) (Hawkins et al, 1987) [ 3 H]-N/OFQ (Dooley and Houghten, 1996),…”
Section: Opioid and Opioid-likementioning
confidence: 99%